KOMPETENSI KEPRIBADIAN GURU DALAM PEMBINAAN AKHLAK SISWA : (Studi Kasus di MTs Al-Ma’arif Brudu Sumobito Jombang) - Nurul Indana (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2021)
Teacher's personality competence is the most important factor for student learning success. Teachers become examples and role models in fostering and shaping students' morals. The purpose of this study was to: a description of the teacher's personality competence in moral development, a description of the process of character building for students at MTs Al Ma'arif Brudu Sumobito Jombang. The results showed that: the teacher's personality competence in building student morals, namely by reflecting the teacher's personality includes: a disciplined personality, being a good role model for students, having a good work ethic by carrying out the mandate and responsibilities as a teacher, being able to behave fair to students in the learning process, be assertive, have a consistent attitude in acting according to norms. The process of building student morals is carried out by various methods applied by the teacher, including: first, through exemplary by instilling discipline and student responsibility. Second, through good habituation by getting students accustomed to worshiping, smiling, greeting, greeting, and shaking hands, and helping each other. Third, give good advice or maui'zhah to students. The fourth is to provide punishment with the aim of deterring students from repeating disgraceful acts.